Rheological properties of wax oleogels rich in high oleic acid - Pehlivanoglu, Halime; Demirci, Mehmet; Toker, Omer Said (TAYLOR & FRANCIS INC, 2018)
Dual and triple combinations of high oleic acid sunflower oil (SO), SO, and blend oil (BO) were used to produce carnauba wax (CW) oleogels (OGs). Fatty acid composition, solid fat content (SFC), and rheological and textural properties of these OGs were determined and compared to laboratory-manufactured margarine. Fatty acid composition, SFC, rheological properties, and firmness value of the OGs were significantly influenced by oil combinations. The storage modulus (G') value was higher than the loss modulus (G'') value in all the OGs. It indicated they are solid-like characteristics. Positive correlation between hardness and A(F) parameter was found.
Keywords: Oleogels; High oleic sunflower; Margarine; Rheological properties; Correlation; SUNFLOWER OIL; MECHANICAL-PROPERTIES; SATURATED FAT; ETHYLCELLULOSE; COMPONENTS; PRODUCT; QUALITY; MODEL; DOUGH; Food Science & Technology